Public Spending In Health Sector in Malawi - Chansa, Collins; Yoo, Katelyn Jison; Nkhoma, Dominic; Piatti, Moritz; Ally, Mariam; Kuguru, Toni Lee; Borrazzo, John; Hettinger, Patrick; Zamawe, Collins Owen Francisco; Schneider, Pia (World Bank, Washington, DC, 2021)
Malawi’s economic growth has been low and volatile for the past two decades, leading to stagnating high poverty levels. The Coronavirus (COVID-19) pandemic will negatively affected economic growth leading to lower government revenue. Despite low per capita growth, Malawi has made strong progress in many areas of human capital development since 2000. Notwithstanding the above, Malawi still faces considerable gaps in human capital, which will impede its ability to reduce poverty in the medium term. Malawi lags behind in some health and nutrition outcomes, including HIV and malaria prevalence. Strengthening human capital in Malawi will be critical to reduce poverty, increase inclusion in society, and create jobs. The World Bank launched a new Human capital index (HCI) in October 2018 as part of its broader Human capital project. One factor that contributes to low human capital outcomes is Malawi’s adolescent fertility rate, one of the highest rates of in the world, with 132 births per 1,000 women aged 15-19. The main underlying cause for the high adolescent fertility rate is the high rate of child marriage. The government is making efforts to strengthen human capital. To strengthen human capital in the face of limited fiscal space, Malawi needs to improve the efficiency and effectiveness of government and donor spending on human capital. To address this problem, there is need to integrate financial reporting systems at district and central government levels. This will enhance government’s ability to monitor and evaluate expenditure and program implementation across sectors.